2021
DOI: 10.1002/brb3.2352
|View full text |Cite
|
Sign up to set email alerts
|

Disease‐inclusive exercise classes improve physical fitness and reduce depressive symptoms in individuals with and without Parkinson's disease—A feasibility study

Abstract: Background and purpose:Exercise is an adjunctive treatment in the management of Parkinson's disease (PD), but barriers such as health status, fear of overexertion, and lack of transportation to the location prevent regular exercise participation. Diseaseinclusive exercise classes may offer an opportunity to make exercise more accessible for older adults with and without diseases. However, the efficacy of such heterogenous exercise classes is still widely unknown. Therefore, it was the aim of this study to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…Several other non-controlled studies, due to lack of proper control not included in our meta-analysis, support the notion that exercise therapy has positive effects on BDNF and various clinical outcomes [ 33 , 34 , 40 , 41 , 42 , 58 , 59 , 60 , 61 ]. Recently, Gomes et al [ 62 ] also showed promising results by studying the effects of High-Intensity Interval Training (HIIT) on BDNF and motor and non-motor outcomes using a single-case experimental design.…”
Section: Discussionsupporting
confidence: 60%
“…Several other non-controlled studies, due to lack of proper control not included in our meta-analysis, support the notion that exercise therapy has positive effects on BDNF and various clinical outcomes [ 33 , 34 , 40 , 41 , 42 , 58 , 59 , 60 , 61 ]. Recently, Gomes et al [ 62 ] also showed promising results by studying the effects of High-Intensity Interval Training (HIIT) on BDNF and motor and non-motor outcomes using a single-case experimental design.…”
Section: Discussionsupporting
confidence: 60%
“…A total of 3,179 records were identified after removing duplicates. Fifty-three studies were considered potentially relevant by screening titles and abstracts and 16 studies (8 two-arm trials ( Frazzitta et al, 2014 ; Freidle et al, 2022 ; Landers et al, 2019 ; O'Callaghan et al, 2020 ; Sajatovic et al, 2017 ; Segura et al, 2020 ; Soke et al, 2021 ; Szymura et al, 2020 ) and 8 single-arm trials ( Oliveira et al, 2020 ; Angelucci et al, 2016 ; da Silva Germanos et al, 2019 ; Harro et al, 2022 ; Ponde et al, 2019 ; Schaeffer et al, 2022 ; Stuckenschneider et al, 2021 ; Zoladz et al, 2014 )), which included a total of 370 patients with PD, were finally deemed eligible for the systematic review. The PRISMA flow diagram illustrating the number of studies excluded at each stage of the systematic review is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that aerobic exercise alone and lower-intensity balance exercises are not effective in reducing insulin resistance and IGF-1 levels in the PD population ( Szymura et al, 2020 ; Soke et al, 2021 ). However, combining aerobic and strength exercises along with multi-modal exercise has been demonstrated to significantly reduce fasting blood glucose levels and increase IGF-1 levels and cognitive abilities ( Krumpolec et al, 2017 ; Stuckenschneider et al, 2021 ). The mixed exercise model thus appears to be more effective in lowering blood sugar levels and improving peripheral insulin resistance in individuals with PD.…”
Section: Exercise Reduces Insulin Resistance and Improves Neurologica...mentioning
confidence: 99%